Information technology use and creativity: Findings from the Children and Technology Project - Jackson, Linda A.; Witt, Edward A.; Games, Alexander Ivan; Fitzgerald, Hiram E.; von Eye, Alexander; Zhao, Yong (Computers in Human Behavior, 2012)
Abstract: This research examined relationships between children’s information technology (IT) use and their creativity. Four types of information technology were considered: computer use, Internet use, videogame playing and cell phone use. A multidimensional measure of creativity was developed based on test of creative thinking. Participants were 491 12-year olds; 53% were female, 34% were African American and 66% were Caucasian American. Results indicated that videogame playing predicted of all measures of creativity. Regardless of gender or race, greater videogame playing was associated with greater creativity. Type of videogame (e.g., violent, interpersonal) was unrelated to videogame effects on creativity. Gender but not race differences were obtained in the amount and type of videogame playing, but not in creativity. Implications of the findings for future research to test the causal relationship between videogame playing and creativity and to identify mediator and moderator variables are discussed.